2019
DOI: 10.3390/nano9101493
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Patternable Graphene Field Emitters for Plasma Displays

Abstract: This paper presents a plasma display device (PDD) based on laser-induced graphene nanoribbons (LIGNs), which were directly fabricated on polyimide sheets. Superior field electron emission (FEE) characteristics, viz. a low turn-on field of 0.44 V/μm and a large field enhancement factor of 4578, were achieved for the LIGNs. Utilizing LIGNs as a cathode in a PDD showed excellent plasma illumination characteristics with a prolonged plasma lifetime stability. Moreover, the LIGN cathodes were directly laser-patterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The hot-shot perovskite solar cells adopted PDI-hGNRs, whose charges were greatly separated, with maximum power conversion efficacy of up to 16.5% . In addition, the GNRs served as field emitters in cathodes exhibited as excellent plasma display devices with a low breakdown field (0.26 V/μm) and high plasma current density (6.2 mA/cm 2 ) . In spite of all these efforts, studies on GNR-based devices still lag behind fundamental research on GNR properties, probably because an unmatched preparation process of devices is pending for further improvements.…”
Section: Performance Control Of Gnrs and Corresponding Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hot-shot perovskite solar cells adopted PDI-hGNRs, whose charges were greatly separated, with maximum power conversion efficacy of up to 16.5% . In addition, the GNRs served as field emitters in cathodes exhibited as excellent plasma display devices with a low breakdown field (0.26 V/μm) and high plasma current density (6.2 mA/cm 2 ) . In spite of all these efforts, studies on GNR-based devices still lag behind fundamental research on GNR properties, probably because an unmatched preparation process of devices is pending for further improvements.…”
Section: Performance Control Of Gnrs and Corresponding Applicationsmentioning
confidence: 99%
“…30 In addition, the GNRs served as field emitters in cathodes exhibited as excellent plasma display devices with a low breakdown field (0.26 V/μm) and high plasma current density (6.2 mA/cm 2 ). 155 In spite of all these efforts, studies on GNR-based devices still lag behind fundamental research on GNR properties, probably because an unmatched preparation process of devices is pending for further improvements. In consideration of current findings, performance control of GNR-based FETs is of easy access through fine preparation for GNRs as smooth structured GNRs offering enhanced functionalities in terms of performance parameters and interpolation of different GNR structures as channels.…”
Section: ■ Performance Control Of Gnrs and Corresponding Applicationsmentioning
confidence: 99%
“…In particular, the uniform distribution of nanorods in BMCD L has large emission sites compared to those in BUNCD L , leading to high electrical conductivity. It is reported that high electrically conducting samples with a high density of emission sites are suitable as cathodes for PD …”
Section: Resultsmentioning
confidence: 99%
“…It is reported that high electrically conducting samples with a high density of emission sites are suitable as cathodes for PD. 45 In order to clarify the effect of the excellent electrical properties of the BMCD and BUNCD series on PD, the PI performance of PD devices was investigated by using BMCD and BUNCD samples as the cathode. The schematic for the PD device using diamond nanostructures as the cathode is shown in Figure 9a.…”
Section: Resultsmentioning
confidence: 99%
“…Graphene and its relative composites can be synthesized via bottom-up and top-down methodologies including chemical vapor deposition (CVD), liquid exfoliation, and electrochemical co-synthesis [ 8 , 9 , 10 , 11 , 12 ]. For graphene materials, the existence of abundant sharp-edged structures can act as efficient field emission sites [ 13 , 14 ]. Nevertheless, field emission from graphene is still a challenge because the fabrication methods such as exfoliation or screen-printing will create graphene sheets laterally on the support substrate, which is unfavorable for electron tunneling.…”
Section: Introductionmentioning
confidence: 99%